Self- Efficacy and its relation with the Types of Classroom Discipline for the Students Teachers A field study on a sample of Students teachers from the faculty of Education / Classroom Teacher/ in Tartous university (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to identify the level of self-efficacy and types of classroom discipline and the relationship between them for the students teachers in the College of Education at Tartous University. Using the descriptive method to validate the research hypotheses, the sampling consisted of (76) male and female students of the Faculty of Education for the year 2015/2016, a questionnaire of Self-efficacy (Slimon, 2004) was used and along with a questionnaire of the types of classroom discipline(Alharahsheh and alkhawaldeh, 2009) after verifying the validity and reliability, and a statistical program for educational and psychological (spss) was used. The research found the following results: the students teachers had a high level of self-efficacy, as the value of mean reached (3.882) with a standard deviation of (0.541) The classroom discipline types had the following order: The indicative type at first (3.850), then the reprimand type(3.276) and the punitive type came at least (2.910). There is also an extrusive positive correlation between the level of self-efficacy and types of classroom discipline. The Self-efficacy was affected by variable of sex but wasn't affected by variable of secondary certificate. And the type of classroom discipline wasn’t affected by variables: sex, and secondary certificate. The researcher concludes a number of suggestions like: training students teachers on the positive classroom discipline skills, and raise their level of self-efficacy, conducting more studies about the subject.